The participation of environmental NGOs in (Austrian) criminal proceedings in the light of Art. 9 (3) Aarhus Convention - Szalk-Unger, Lara (The Opole Studies in Administration and Law, 2022)
One of the three main pillars of the Aarhus Convention is access to justice for members of the public. Access to justice can not only be provided for in administrative proceedings but also via criminal proceedings in cases of environmental crime. Members of the public with an interest in environmental protection are especially environmental NGOs. In some European countries NGOs play an active role in criminal proceedings, however in many they are banished to the sidelines. This article describes the implications and requirements of Art. 9 (3) of the Aarhus Convention for access to justice via criminal proceedings, analyzes the existing ways for environmental NGOs to participate in Austrian criminal proceedings and presents ways in which criminal procedure law can be reformed to meet the requirements of the Aarhus Convention. The end goal is to make the prosecution of environmental crime as effective as possible.